2012
DOI: 10.1111/j.1747-0285.2012.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activity of steroidal chalcones: evaluation of their effect on hemozoin synthesis and the new permeation pathway of Plasmodium falciparum‐infected erythrocyte membrane

Abstract: Chalcone derivatives on an estradiol framework were evaluated for their ability to inhibit the growth and development of the malaria parasite Plasmodium falciparum. Out of twelve steroidal chalcones and one indanone derivative studied, three were found to have 50% growth inhibitory concentration less than 5 lM and minimum inhibitory concentration for parasite development from ring to schizont stage as £20 lM with best activity for gallic acid-based chalcone derivative 1 as 2.07 and 10 lM, respectively. Two of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Similar results were shown in the previous studies where different chalcone derivatives showed hindrance of plasmodial haemozoin formation in culture suggesting that these chalcones act on haemozoin formation pathways [5254]. However, few studies reported that some do not interfere with haemozoin formation [55, 56]. This variation is mostly due to substitution on the ring A or B of the chalcones.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were shown in the previous studies where different chalcone derivatives showed hindrance of plasmodial haemozoin formation in culture suggesting that these chalcones act on haemozoin formation pathways [5254]. However, few studies reported that some do not interfere with haemozoin formation [55, 56]. This variation is mostly due to substitution on the ring A or B of the chalcones.…”
Section: Discussionsupporting
confidence: 87%
“…[15] According to the same authors, the ability of these NPPB derivatives to inhibit NPP improves with the length and lipophilicity of the hydrophobic tail. Chalcones like 11 are structurally related to the cinnamoyl moiety and were also reported as NPP inhibitors by Go et al [16] and Sisodia et al [17] In compounds 7, the heterocyclic core is linked to a butylcinnamoyl group that reasonably matches relevant structural factors described above, reinforcing the structural suitability of the compounds as NPP inhibitors. Heme seems to be a main target of compounds 7, which agrees with their structural similarity to chloroquine.…”
supporting
confidence: 55%
“…Over the past ten years, there has been increasing attention to chalcones because they exhibit diverse biological activities. Naturally occurring chalcones, as well as synthetic chalcone analogues, have been demonstrated to have many biological effects, including anti‐inflammatory , anti‐malarial , anti‐fungal , and anti‐oxidant/anti‐cancer activities . Recent data suggest that chalcones also target a number of cancer signaling pathways, including tubulin polymerization, proteasomal pathway, cell cycle, apoptosis, receptors, and multidrug resistance transporters .…”
Section: Introductionmentioning
confidence: 99%